Detection of influenza C virus by a real‐time RT‐PCR assay. Issue 6 (27th February 2013) - Pabbaraju, Kanti; Wong, Sallene; Wong, Anita; May‐Hadford, Jennifer; Tellier, Raymond; Fonseca, Kevin
<x xml:space="preserve">Abstract</x> Background Influenza C virus can cause both upper and lower respiratory tract infections and has been reported to be prevalent in children. However, these infections have been under‐diagnosed, and epidemiological data available are limited due to the lack of convenient detection assays. Objective Design and validate a real‐time reverse‐transcriptase PCR (rt RT‐PCR) assay for the detection of influenza C. Study design Respiratory samples from two primary settings, namely, children who were hospitalized or seen in the emergency department, and respiratory outbreaks for which no other viral etiology was found were used for the detection of influenza C. Results and Conclusions The assay was sensitive and specific for the detection of influenza C. Eleven of 474 (2·32%) patients, all less than 10 years of age, were positive for influenza C. The strains clustered into two lineages, namely C/Kanagawa and C/Sao Paulo, based upon sequencing of the hemagglutinin‐esterase gene. Epidemiological data showed that a higher proportion of influenza C infections occur in younger children and during the winter months. This is the first report of the detection of influenza C in Alberta, Canada, and suggests that the detection of this virus should be included in respiratory virus testing panels.